Light drinking during pregnancy: Social advantages explain positive correlates with child and early adolescent adjustment. (November 2019) - Barbuscia, Anna; Staff, Jeremy; Ploubidis, George B.; Fitzsimons, Emla; Maggs, Jennifer
Abstract: Maternal heavy alcohol use during pregnancy is harmful to offspring's health and adjustment. However, findings from studies on lower levels of prenatal drinking are mixed; a few even predict positive cognitive and psychosocial outcomes. Given that alcohol is a neurotoxin and teratogen, scholars question developmental benefits and point to residual confounding as a potential explanation, particularly as light drinkers are positively selected with respect to health and socioeconomic status. Using prospective, intergenerational data from the nationally-representative Millennium Cohort Study (MCS) in the United Kingdom, we studied associations between mother's drinking during pregnancy and children's cognitive and psychosocial outcomes at ages 3, 5, 7, 11, and 14 years ( n = 10, 454). We included early life confounders (e.g., maternal education, health, smoking) and mother's cognitive ability, and assessed robustness of relationships across outcomes and alternate drinking classifications. Results of a series of multivariable regression models found no association between light drinking and cognitive and psychosocial outcomes up to and including the age of 14, after controlling for key confounders. Light drinking during pregnancy was linked to higher socioeconomic advantages (e.g., mothers' higher education, professional/managerial occupation, home ownership, cognitive scores), which together accounted for positive associations between light drinking and children's outcomes. Mother's cognitive ability was an especially important confounder. Highlights: Health guidelines proscribe alcohol use during pregnancy due to teratogenic effects. Some work suggests limited positive child outcomes after light maternal drinking. Longitudinal UK cohort study observes light drinking mothers are socially advantaged. No positive correlates of light prenatal drinking after confounders controlled. Mother cognitive skills key explanation of apparent benefits of light drinking.